Kajian Infrastruktur Persampahan di Kawasan Pemukiman Mayarakat dengan Pendapatan Rendah Kecamatan Kertapati Kota Palembang - Sepriyati Anggraini (Jurnal Teknik Sipil dan Lingkungan, 2014)
Kertapati is one of area with high level of crowded in Palembang. As long as higher significant development of daily needed of society, caused rubbish stacked. This research used 3 sample from Kertapati’s area : Kemang Agung, Kemas Rindo, and Ogan Baru. The purpose of this research were to find out the increasing of rubbish for 5 years, to know the infrastructure needed by those areas and to find out the influence of low level salary toward rubbish volume and the way in processing the rubbish. It used Microsoft excel, linier geometric method to count the total of citizens in the next 5 years, the statistic and sampling method to analyze the data of total sample on the questionair that will be distributed to the respondent. In 2013, total projection society of Kertapati’s area for district is 53.156 people with volume from rubbish stacked 146,179 m3/day, trashcan needed is 24 container with capacity 6 m 3, 10 dump truck and 41 rubbish motorcycle.While for 2018, there is improvementin total number of society as much 55.696 people with volume from rubbish stacked is 153, 164 m3/day, trashcan needed is 26 container with capacity 6 m3, 11 dump truck and 42 rubbish motorcycle. Based on research observation, it is program system of rubbish collected individual indirectly and collected by using SCS (Stationary Container System) method. So that’s why, the improvement of transportation program system of rubbish collected can create job vacancy, additional salary and could make safe, cozy and healthy environment. Keywords: infrastructure, rubbish,TPS, volume of rubbish, processing the rubbish